Improving the market success of Ethiopian farmers in dairy value chains - International Livestock Research Institute (International Livestock Research Institute, 2010)
Speaking at the opening of the National dairy forum on 23 November 2010, improving market success of Ethiopian farmers (IPMS) Project Manager, Dirk Hoekstra presented some IPMS experiences in the research for development in the dairy value chain. He said that, if I need to stress a few points, we should start paying attention not on a single part of the dairy value chain (fluid milk market) which you see on urban centers only. We should also pay attention on the dairy value chain in the rural areas where dairy animals are kept both for dairy purposes and in particular for butter and meat. In conclusion he said that development should pay attention to different systems and organizational and institutional interventions.